Nanotechnology development in electric vehicles: a bibliometric analysis (2001–2024) - M. Nanthakumar; S. Raja (Discover Sustainability)
Abstract Nanotechnology has significantly enhanced electric vehicles (EVs) performance, particularly in areas such as battery efficiency and energy storage. EVs are increasingly viewed as a critical component in global strategies to mitigate climate change. This study conducts a bibliometric analysis of nanotechnology research related to electric vehicle from 2001 to 2024 using data retrieved from the Web of Science database (n = 18,496). The analysis was performed using VOSviewer and biblioshiny to map publication trends, international collaborations, and the influence of socioeconomic factors. The findings reveal a strong correlation (r = 0.734) between national R&D investment and publication output in this domain. China leads in research output (46.48%), followed by the United States, Germany, and India. Interestingly, while the United States has the highest R&D expenditure, it contributes comparatively fewer publications in this niche. Electric vehicles rely heavily on lithium batteries, and as a result, nanotechnology plays a key role in thermal management, preventing battery degradation. Keyword clusters show that carbon nanomaterials and nanofibers exhibit higher energy efficiency than alumina. Carbon nanomaterials are an efficient approach to control CO2 emissions and energy conversion solutions. Graphical abstract